Um problema elíptico com expoente crítico de Sobolev - Ricardo, Cleiton de Lima (2014)
In this work we studied existence of positive solutions for an elliptic problem with critical Sobolev exponent (-u = up + f(x; u) em u = 0 sobre @ that vanishes on the boundary of a bounded domain of Rn. The nonlinearity f(x; u) has subcritical growth. This is done by showing that the minimax level is below a constant that depends only on the dimension of the domain and the best Sobolev constant.